(untitled) (International Journal of Engineering Materials and Manufacture, 2018)
Metal stamping industry has Quick Die Change (QDC) as a form of Single Minutes Exchange of Dies (SMED) as an efficient production technique where the implementation depends on operator’s activities, clamping system, accessories type and position, etc. This QDC could apply to improve the process efficiency, control of inventory and reducing the cost. This research compared the traditional metal stamping process and QDC System (QDCS) of metal stamping. This research was using Focused Group Discussion (FGD), direct observation and experiments, conducted in a private metal stamping company in wider Jakarta region of Indonesia. It was observed that the QDCS significantly reduces setup time, storage space and the cost. The setup time and cost reduced to one third of the conventional and the requirement of storage decreased by 70%. In addition, QDCS reduces the waste significantly.